Método teórico experimental para la evaluación de colectores solares de placa plana en viviendas unifamiliares en la ciudad de Guayaquil. - Vargas Ferruzola, Carlos Luís (2017)
The use of hot water in single-family homes has been increasing and to meet the demand implies high energy consumption either this electric or petroleum-based fuels, which requires a system that satisfies the demand with a decrease in energy consumption and protection environment. In this project an experimental theoretical analysis of flat plate solar collectors is made based on the main variables involved in the process, for its implementation in single family dwellings. The procedure described allows the selection of the collectors and the calculation of their efficiency, is applicable to the conditions of the city of Guayaquil. The angle of inclination of the collector where the maximum efficiency is reached is 150, this coincides with the criteria of the literature where it is established that the angle of inclination of the collector must be between 100 and 150 above the latitude of the place. The maximum average efficiency achieved experimentally in the flat solar collector is 30.12%. The recovery time of the investment by energy saving in the use of a renewable energy source is of 7.19 years, to this it is necessary to add the almost null environmental impact that causes the use of this type of energy and the durability Estimated from flat solar collectors that is 25 years. Due to the above, it is considered viable the project for the heating of water in singlefamily homes.